Long-term reinterventions after Thulium laser enucleation of the prostate: 12-year experience with more than 1000 patients : benign prostatic enlargement - Grüne, Britta; Siegel, Fabian; Waldbillig, Frank; Pfalzgraf, Daniel Philipp; Kamdje Wabo, Gaetan; Herrmann, Jonas; Kriegmair, Maximilian; Nuhn, Philipp; Michel, Maurice Stephan; Hardenberg, Jost von (European urology focus, 2022)
Background - Thulium laser enucleation of the prostate (ThuLEP) is an established treatment option for benign prostatic enlargement (BPE), but long-term outcomes have not yet been reported. - Objective - To prove the durability of ThuLEP by investigating its long-term efficacy and morbidity. - Design, setting, and participants - All patients who underwent ThuLEP at a German tertiary referral center between 2009 and 2021 were retrospectively followed up for reinterventions for persistence or regrowth of prostate adenoma (ReIP) or long-term complications (ReIC). - Intervention - ThuLEP. - Outcome measurements and statistical analysis - We calculated the cumulative incidence for ReIP and ReIC at 10 yr. Univariate and multivariate Cox regression models were constructed to identify predictors of ReIP and ReIC. - Results and limitations - Overall, 1097 patients underwent ThuLEP. The median overall follow-up was 6.0 yr (interquartile range [IQR] 2.4-9.2). For one-third of patients (n = 369), median follow-up of 10 yr (IQR 9.1-11.2) was available. A total of 42 patients (3.8%) underwent ReIP after a median of 2 yr (IQR 0.3-4.9). The rate of long-term ReIC was 2.6% (n = 29) and the median time to ReIC was 0.5 yr (IQR 0.3-1.7). The most frequent ReIC was urethrotomy (n = 16, 1.5%). The cumulative incidence of ReIP and ReIC at 10 yr was estimated at 5.6% and 3.4%, respectively. Enucleation weight ≥60 g was a significant predictor of ReIP (hazard ratio 1.2, p = 0.014). The retrospective study design and the lack of functional outcomes are the main limitations. - Conclusions - ThuLEP is a durably effective and safe procedure with low reintervention rates within 12 yr. - Patient summary - This study investigated long-term outcomes of thulium laser enucleation of the prostate for benign enlargement of the prostate (BPE). Low rates of repeat treatment for BPE recurrence or for other complications were observed. Our results show the safety and efficacy of this treatment over a period of 12 years.